2005
DOI: 10.1016/j.cell.2005.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Passenger-Strand Cleavage Facilitates Assembly of siRNA into Ago2-Containing RNAi Enzyme Complexes

Abstract: In the Drosophila and mammalian RNA interference pathways, siRNAs direct the protein Argonaute2 (Ago2) to cleave corresponding mRNA targets, silencing their expression. Ago2 is the catalytic component of the RNAi enzyme complex, RISC. For each siRNA duplex, only one strand, the guide, is assembled into the active RISC; the other strand, the passenger, is destroyed. An ATP-dependent helicase has been proposed first to separate the two siRNA strands, then the resulting single-stranded guide is thought to bind Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
783
7
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,004 publications
(838 citation statements)
references
References 54 publications
25
783
7
11
Order By: Relevance
“…Pre-miRNA hairpin precursor is exported into the cytoplasm by the Exportin-5/Ran-GTP complex 28,29 and is then bound by the RISC Loading Complex (RLC) containing Dicer, TRBP, and Ago2. [30][31][32] Dicer cleaves the pre-miRNA into the mature miRNA, which enters the RISC complex and binds to complementary sequences within the 3 0 -UTR of the target mRNA. 33,34 RISC-bound mRNA transcripts may be suppressed in protein translation, destabilized by deadenylation, or degraded by Ago2 RNase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-miRNA hairpin precursor is exported into the cytoplasm by the Exportin-5/Ran-GTP complex 28,29 and is then bound by the RISC Loading Complex (RLC) containing Dicer, TRBP, and Ago2. [30][31][32] Dicer cleaves the pre-miRNA into the mature miRNA, which enters the RISC complex and binds to complementary sequences within the 3 0 -UTR of the target mRNA. 33,34 RISC-bound mRNA transcripts may be suppressed in protein translation, destabilized by deadenylation, or degraded by Ago2 RNase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact, that the recombinant hAgo2 are not capable of unwinding short RNA duplexes, genetic data in flies suggest that Ago2 is indispensable for this process (Okamura et al, 2004). In fact, it has been recently demonstrated that the cleavage competent fly and the human Ago2 actively participate in the unwinding mechanism by cleaving the passenger strand of the perfectly double-stranded siRNA (Matranga et al, 2005;Miyoshi et al, 2005;Leuschner et al, 2006).…”
Section: Risc Formationmentioning
confidence: 99%
“…Members of the Argonaute-Piwi (Ago-Piwi) family of proteins are core components of the RISC and some of these polypeptides function as siRNA-guided endonucleases (Baumberger and Baulcombe 2005;Hammond et al 2001;Liu et al 2004a;Qi et al 2005;Tomari and Zamore 2005). Recent evidence suggests that a siRNA duplex may be loaded into RISC and then Ago cleaves one of the siRNA strands (the passenger strand) triggering its dissociation from the complex (Matranga et al 2005;Miyoshi et al 2005;Rand et al 2005). Activated RISC then functions as a multiple-turnover enzyme that recognizes and cleaves RNA molecules complementary to the incorporated single-stranded guide siRNA Sontheimer 2005;Tomari and Zamore 2005).…”
Section: Introductionmentioning
confidence: 99%